Electron, spin and momentum densities and chemical reactivity - Mezey, Paul G.; Robertson, Beverly E. (Understanding chemical reactivity, 2000)
The electron density of a nondegenerate ground state system determines essentially all physical properties of the system. This statement of the Hohenberg-Kohn theorem of Density Functional Theory plays an exceptionally important role among all the fundamental relations of molecular physics. Electron densities provide detailed information that gives important insight into the fundamentals of molecular structure and a better understanding of chemical reactions. If the functional form of a molecular electron density is known, then various molecular properties affecting reactivity can be determined by quantum chemical computational techniques or alternative approximate methods. This book contains a selection of chapters based on papers given at the 12th conference of the Commission of Charge, Spin and Momentum Density of the International Union for Crystallography, held in Waskiesiu, Prince Albert National Park, Canada, on July 27 - August 1, 1997. The choice of topics represents some of the latest advances in the field of electron, spin, and momentum densities and the analysis of these densities with respect to their roles in determining chemical reactivity. This book provides an exciting collection of accounts of the latest advances, and also provides further motivation for new research to address some of the challenging, unsolved problems of the fascinating interrelations between electron, spin, and momentum densities, and the complex subject of chemical reactivity.